Diagnosis and treatment of mechanical bowel obstruction (Colombia Medica, 1989)
Were admitted 166 patients to the Hospital Universitario del Valle with a clinical diagnosis of mechanical bowel obstruction in 1983; 64.5% of patients were male, and only 39% of cases consulted less than 24 hours between the onset of symptoms and admission. The more frequent symptoms and signs were abdominal pain (86%), nausea and vomiting (79%), and abdominal distension (69%). Plain X-ray abdominal films showed signs of intestinal obstruction in 47%, even though 40% of patients had incarcerated inguinal hernias, and films were not taken in the majority of patients.The etiology for the obstruction was external hernias in 40.4%, postsurgical adhesions in 25.9%, congenital lesions in 14.5%, intussusception in 6.6%, malignancy in 3.6%, and others in 9%. The intestines were normal in 44.6%, intestinal ischemia in 40.4%, and necrosis in 15%. The vast majority of obstructions were located at the ileon. The overall frequency of complications was 21.6%, and mortality was 2.4%. The average hospital stay was 6.3 days.